The ANALYSIS OF THE INFLUENCE OF CREATIVE INDUSTRY ON THE ECONOMIC DEVELOPMENT OF COMMUNITY ENTERPRISES IN THE SUKABUMI REGION: Innovation and Creativity for Local Economic Development in Sukabumi - Zaki, Muhammad Zaki Hibatullah; Icuh Komala, Icuh Komala (JURNAL Dasarrupa: Desain dan Seni Rupa, 2024)
This study analyzes the impact of the creative industry on the economic development of the communit in the Sukabumi region, focusing on the role of digital marketing as a key driver. Employing a qualitative descriptive approach, data was colleected through in-depth intervies with industry players (INFOSMI HRD, Cimol Bojot Uwa vendor), fields observations, and documentation studies from local government. Findings indicate that the creative industry in Sukabumi experienced significant groth in 2024-2025, particularly in the culinary, fashion, and digital media sectors. Digital marketing proved crucial in enhancing brand awareness and expanding market reach for MSMEs, which in turn created new job opportunities and stimulated local economic growth. Nevertheless, challenges such as low digital literacy, limited capital, and uneven internet infrastucture in the regency areas still impedee optimal developmeent. Therefore, collaborative strategies, adaptation to market trends, and strengthening digital literacy are recommended to ensure the suistanable growth of the creative industry in Sukabumi.